MSM36 raw data of EM122 multibeam echosounder (bathymetry, beam time series & water column data) for the Alboran Sea - Dierk Hebbeln; Stefanie Gaide (PANGAEA, 2018)
Multibeam echosounder (MBES) data recorded during RV MARIA S. MERIAN cruise MSM36 between 18.02.2014 and 17.03.2014 at the Moroccan continental margins. The cruise carried out multidisciplinary research on the long-term development of cold-water coral ecosystems in selected areas along the Moroccan continental margins in the Mediterranean Sea and in the Atlantic Ocean. The key instrument to be used during this expedition was the Bremen Deep Sea Drill Rig MeBo. CI Citation: Paul Wintersteller (seafloor-imaging@marum.de) as responsible party for bathymetry raw data ingest and approval. Description of data source: During the RV MARIA S. MERIAN cruise MSM36, the Kongsberg EM122 multibeam echosounder with a nominal sounding frequency of 12 kHz was utilized. 288 beams with an acoustical footprint of 2°(TX)/2°(RX) are formed for each ping. For further information consult https://www.km.kongsberg.com/. During the cruise the swath width was set to 120° and the survey speed was kept at around 8 knots. The use of the high-density equidistant and the dual-swath mode of the EM122 resulted in up to 864 soundings per ping. Both MBES devices (EM1002 and EM122) were used for the seabed mapping in the Mediterranean Sea. Though, the acquisition computer of the EM122 failed west of Melilla but could be repaired before entering the Atlantic region. The rest of the time the system was stable. In the Gulf of Cádiz, the seabed mapping was only conducted with the EM122 as the water depth was too deep for the EM1002. Two different subsets of hydroacoustic data were acquired during this cruise: A western Mediterranean Sea dataset covering the EMCP (East Melilla Cold-Water Coral Province) and the WMCP (West Melilla Cold-Water Coral Province) in the Alboran Sea and an Atlantic dataset covering the MACP (Moroccan Atlantic Cold-Water Coral Province) in the Gulf of Cádiz. Responsible person during this cruise / PI: Stefanie Gaide (sgaide@marum.de). Chief Scientist: D. Hebbeln CR: https://www.tib.eu/de/suchen/id/awi%3Adoi~10.2312%252Fcr_msm36/ CSR: http://www.bsh.de/aktdat/dod/fahrtergebnis/2014/20140066.htm A special thanks goes to the watch keeper during MSM36: J.P. Henriet, N. Stange